Attainment of Student Engagement in Secondary Schools in Kerala: An Empirical Investigation - Parekkadan House, P J Sabu; Deepa Roy, (Indian Journal of Extension Education, 2025)
High quality of school education can contribute significantly to socio-economic development of a region. In Kerala, quantitative parameters such as highest gross enrolment ratio (GER) and lowest dropout rate in school education are ideal. At the same time, Kerala's performance in terms of qualitative benchmarks such as student learning outcomes (SLOs) and equity are at sub-optimum. Conceptually quality is positively related to the achievement of SLOs, which in turn requires attainment of student engagement in learning (SEL). There is limited research on determinants of SEL in school education in Kerala. The present study aimed to investigate the SEL in Kerala. To achieve the goal, collected primary data from 584 students of private-aided schools (PASs) and state-government schools (SGSs) during the period from July 2024 to November 2024 were collected. To analyze the data,statistical tools such as Mean, Standard Deviation and F-test were used. The study found that selected variables such as mother’s education, social-group and type of school of the students had significant impact on student engagement in learning in Kerala.Based on the findings, the paper recommends that the Government and School administration should implement initiatives to improve student engagement in learning in an effective and equitable manner in Kerala.